Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4414/smw.2011.13268
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of cytosol expression of 8-OHdG in normal renal tubules is associated with the severity of renal fibrosis

Abstract: This study demonstrated that the intensity of 8-OHdG expression in NTc was associated with the severity of renal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The strong correlation between serum concentration of 8-OHdG and PASI score in patients with severe psoriasis and the correlation between 8-OHdG levels and markers of renal impairment suggest that 8-OHdG could favour the onset and/or development of renal disease in patients with psoriasis. In medical literature, there are limited data on the role of 8-OHdG in progressive renal fibrosis (59,60), hypertension associated with proteinuria (61), chronic renal failure (62), diabetes associated with proteinuria (63,64), bladder cancer (65), renal cancer (66) and urothelial carcinoma (67).…”
Section: Psoriasis Vulgaris Pasi Score ------------------------------mentioning
confidence: 99%
“…The strong correlation between serum concentration of 8-OHdG and PASI score in patients with severe psoriasis and the correlation between 8-OHdG levels and markers of renal impairment suggest that 8-OHdG could favour the onset and/or development of renal disease in patients with psoriasis. In medical literature, there are limited data on the role of 8-OHdG in progressive renal fibrosis (59,60), hypertension associated with proteinuria (61), chronic renal failure (62), diabetes associated with proteinuria (63,64), bladder cancer (65), renal cancer (66) and urothelial carcinoma (67).…”
Section: Psoriasis Vulgaris Pasi Score ------------------------------mentioning
confidence: 99%
“…Urinary angiotensinogen levels were also significantly correlated with urinary α1-microglobulin, a marker of proximal tubular injury which is believed to be one of the earliest markers of tubular dysfunction 29 . Urinary excretion of 8-hydroxydeoxyguanosine (8-OHdG), a marker of oxidative DNA damage associated with glomerular and interstitial fibrosis 30 , is also increased in stone formers 31 . Furthermore, immunohistochemical analysis demonstrates increased 8-OHdG expression in the renal tissue adjacent to stone in subjects with nephrolithiasis 32 .…”
Section: Evidence For Impairment Of Normal Kidney Functionmentioning
confidence: 99%
“…Research has shown that 8-OHdG is increased in the tissues, serum and/or urine of patients with oxidative stress-associated diseases. [53][54][55] Damage to genetic material can be heritable and is associated with negative effects to cells, such as tumour generation.…”
Section: Resultsmentioning
confidence: 99%